impact of globalization on social Fragmentation and urban violence in the city of lima (2009-2012) - Ramírez Miranda, Durga Edelmira (2013)
The objective of this research is to determine the impact of globalization on social fragmentation and urban violence in the city of Lima in the period 2009-2012. Research is applied and descriptive level. Techniques were used interview, observation, content analysis. We analyze the indicators through which society perceives Lima is fragmented and that urban violence is manifested increasingly in the context of globalization and advanced modernization. There is a polycentric metropolitan growth expanded and fragmenting the urban neighborhoods excluded leaving functional networks of the city that are cause and consequence of social fragmentation processes, which isolate and separate the different social groups in segregated areas with little chance of integration and development. Lima case is analyzed, understood as a good example of the context of globalization noted, as well as processes of social fragmentation and urban violence.